2012
DOI: 10.1002/ejsp.1886
|View full text |Cite
|
Sign up to set email alerts
|

Collective regret versus collective guilt: Different emotional reactions to historical atrocities

Abstract: A distinction between guilt and regret in reactions to in‐group atrocities is proposed. Four studies (total N = 1249) support the notion that guilt and regret are distinct emotional reactions. Whereas guilt is a self‐focused, aversive emotional reaction following from appraisals of responsibility and associated with the intention to make amends, regret follows from an empathic victim perspective, is less aversive, and is more strongly associated with positive attitudes towards the victim groups and the intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 77 publications
9
84
1
1
Order By: Relevance
“…Past research revealed the emergence of group-based emotions such as shame, guilt or regret in various countries and referring to different cases of historical injustices Doosje, Branscombe, Spears, & Manstead, 1998;Gausel, Leach, Vignoles, & Brown, 2012;Imhoff et al, 2012). Referring to the Holocaust in particular, Peetz et Therefore, they were in the focus of the current research.…”
Section: Group-based Emotions In the Context Of The Holocaustmentioning
confidence: 93%
See 3 more Smart Citations
“…Past research revealed the emergence of group-based emotions such as shame, guilt or regret in various countries and referring to different cases of historical injustices Doosje, Branscombe, Spears, & Manstead, 1998;Gausel, Leach, Vignoles, & Brown, 2012;Imhoff et al, 2012). Referring to the Holocaust in particular, Peetz et Therefore, they were in the focus of the current research.…”
Section: Group-based Emotions In the Context Of The Holocaustmentioning
confidence: 93%
“…In contrast to former studies on group-based emotions in the context of the Holocaust that used artificial stimulus material or vignettes (Imhoff, Bilewicz, & Erb, 2012;Peetz, Gunn, & Wilson, 2010), this field study focuses on film material that was actually broadcasted and critically discussed in Germany. Starting from the critique of the influencing mechanisms of specific films and TV documentaries, the current study is carried out in two major steps.…”
Section: Journal Of Social and Political Psychology Jspppsychopeneumentioning
confidence: 99%
See 2 more Smart Citations
“…Such teaching will enlarge the notion of historical literacy into a study of historical culture (Grever and Stuurman 2007) and historical consciousness (Rüsen 2004) in the classroom so that students become reflective of the role of collective memory and history teaching in processes of conflict transformation and understand the ways in which various forms of historical consciousness relate the past, present and future (Van Alphen and Carretero 2015;Psaltis 2016). This can be done through a better grasp of the way attributions of past wrongdoings (Doosje and Branscombe 2003) relate to processes of moral disengagement, apology, guilt, shame or regret (Imhoff et al 2012); how realistic and symbolic threats can become an obstacle for prejudice reduction, confidence building and reconciliation; and how intergroup contact can lead to reconciliation. This kind of history teaching is interdisciplinary in nature and can be called transformative history teaching to the extent that it facilitates both the cultivation of historical thinking and conflict transformation.…”
Section: Conflict Transformation Conflict Resolution and Reconciliatmentioning
confidence: 99%